Xanthoma Disseminatum In a Pair of Blind, Deaf Male Twins. (15th March 2011) - Natanzi, Naveed; Peng, David; Ahdoot, Eli; Ghatan, Sandra; Reinstandler, Amy; Ram, Ramin
Abstract : Xanthoma disseminatum (XD) is a rare normolipemic histiocytic disorder of non-Langerhans cell origin characterized by erythematous to tan/brown papules in flexor surfaces. Considered a generally benign, chronic disease of unknown etiology, XD typically affects the skin, mucous membranes, and less commonly, other organs. To date, there has been no typical or consistent inheritance pattern described, nor has it ever been considered as a component of any known syndrome. We describe, for the first time, two cases of XD in a pair of blind and deaf twin brothers.